WORKING ENVIRONMENT AND EFFORT-REWARD IMBALANCE IN THE FINANCIAL SECTOR - Fedorenko , Andrii (Socio-economic relations in the digital society, 2021)
In the context of globalization and growing demands to the employee, it is important to maintain the health and well-being of a person in the workplace. The article discusses the possibility of regulating the level of stress and effort, as well as the balance of effort-reward within the framework of the effort-reward imbalance (ERI) model. The purpose of this article is to identify the relationship between individual factors of the work environment and the assessment of the appropriateness of effort and reward within the ERI model. The study examines the relation between the characteristics of work environment and level of stress at work, the applied effort. The study is based on the responses of 1 148 people working in the financial sector in 35 European countries. The survey was conducted as part of the European Working Conditions Survey 2015 (EWCS 2015). To find the relationship between the factors of the work environment and the components of the ERI model, 18 questions from the EWCS 2015 questionnaire were selected. The result of the correlation analysis shows: a weak link between stress level and balance of effort-reward; a moderate relationship between fairness assessment and a balance of effort-reward; a weak link between fairness and stress level. The relationship of employee effort and stress level to specific factors in the work environment (autonomy, tasks discretion and feedback, employee voice, good management practices, flexibility of work schedule, training, social support) is weak or absent. The social support and good management practices have a link with the reward component of the ERI model. Improvements in the work environment do not affect stress level and decreased employee effort. Stress and strain are necessary to get the job done. Social support and good management practices are perceived by employees in relation to the reward component of the ERI model. Regulation of the effort-reward balance is possible due to factors of reward, social support, good management practices.